In-vitro studies on antioxidant and antidiabetic potential of Sesoot (Garcinia picrorrhiza Miq.) fruit ethanolic extract from Indonesia - Sri Utami; Sonny Pamuji Laksono; Qomariyah Romadhiyani Sachrowardi; Dewi Nurul Mustaqimah; Susi Endrini; Ndaru Andri Damayanti; Said Nafik; Betharie Cendera Arrahmani; Hanna Sari Widya Kusuma; Wahyu Widowati (Universitas Ahmad Dahlan, 2021)
Diabetes mellitus (DM) is a disease that can be identified by high levels of blood glucose. Garcinia plants have been widely used for many traditional medicines as antioxidant, anticancer, antidiabetics, and antiinflammation. The antioxidant and antidiabetic activities of (Garcinia picrorrhiza Miq.) or sesoot fruit extract were evaluated in this study and compared with xanthone. The antioxidant and antidiabetic of ethanolic ripe sesoot (G. picrorrhiza Miq.) fruit extract (GpKar) was evaluated by (ABTS) reducing activity, α-glucosidase, β-glucosidase, and α-amylase inhibitor activity. GpKar showed higher ABTS-reducing activity (IC50 = 49.30 µg/mL) than xanthone (IC50 = 404.30 µg/mL). GpKar showed IC50 = 109.32 µg/mL for α-glucosidase inhibitory activity, while xanthones had a better activity (IC50 = 33.97 µg/mL). GpKar also showed lower α-amylase inhibitory activity and β-glucosidase (IC50 = 126.01 and 9432.09 µg/mL) compared to xanthone (IC50 = 44.32 and 405.03 µg/mL, respectively). The compounds of GpKar are proven to have antioxidant and antidiabetic activities. Therefore, it will be industrially relevant to develop a natural medicine for decreasing DM risk, thus evaluating the antioxidant and antidiabetic effect of G. picrorrhiza by a pre-clinic study is needed.